Program Pengabdian Masyarakat Melalui Gantungan Cinta Sebagai Daya Tarik Wisata Sumber Biru - Dhian Satria Yudha Kartika; Muhamad Raafi Al Hadi Mubarrok; Salma Salsabila Sirsya; Hardiva Aura Jingganingsandya; Khansa Xena Nirwasita; Safina Najah (Universitas Maritim AMNI Semarang, 2023)
The development of tourism in each region is indeed a trend that occurs in many districts or cities. Wonomerto Village also has various tourism potentials such as the Sumber Biru Tourism Area and the Tomb of Prince Benowo which have become economic drivers for the local community. The addition of a new spot at Sumber Biru Tourism Area is a good step to continue to increase the attractiveness of this tourist destination. The Participatory Action Research method can be an effective approach in the development process. In this context, community participation can involve them in the planning, decision-making and implementation processes of tourism development projects. Communities can provide valuable input, ideas and local knowledge in identifying tourism potential that has not been fully utilized around the Sumber Biru Tourism Area. In addition, involving the community in tourism development activities can also open up opportunities for them to be involved economically, for example through micro-enterprises or local crafts that support the tourism sector. This can increase the income of the local community and encourage sustainable economic development in Wonomerto Village.